Antioxidant and Hepatoprotective Potentiality of Randia dumetorum Lam. Leaf and Bark via Inhibition of Oxidative Stress and Inflammatory Cytokines - Kandimalla, Raghuram; Kalita, Sanjeeb; Saikia, Bikas; Choudhury, Bhaswati; Singh, Yogendra P.; Kalita, Kasturi; Dash, Suvakanta; Kotoky, Jibon (Frontiers in Pharmacology, 2016)
Randia dumetorum Lam. (RD) (Rubiaceae) is traditionally used by some tribes of Assam and Manipur of North East India for the treatment of liver ailments. In this context, to scientifically validate this indigenous traditional knowledge, we have evaluated the antioxidant and hepatoprotective activity of RD leaf and bark. The methanol extracts of RD leaf and bark were evaluated for in vitro antioxidant activity which exhibited good anti-oxidant activity in terms of reducing power assay, total antioxidant assay and DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavenging assay. Total phenolic and flavonoid content were found to be 112 ± 3.24 mg and 138 ± 2.46 mg gallic acid equivalents/g extract and 2.6 ± 0.26 mg and 3.34 ± 0.31 mg rutin equivalents/g extract respectively for RD leaf and bark methanol extracts. The In vivo hepato protective activity of the RD leaf and bark extract was evaluated against carbon tetrachloride (CCl4) induced hepatic damage in male wistar rats. CCl4 administration induced hepatic damage in rats resulted in increased levels of aspartate transaminase, alanine transaminase, alkaline phosphatase, lactate dehydrogenase, thiobarbituric acid reacting substances, albumin, bilirubin, TNF-α, IL-1β and decreased levels of total protein and antioxidant enzymes like superoxide dismutase, catalase and glutathione reductase. RD leaf and bark methanol extracts pre-treatment exhibited protection against CCl4 induced hepatotoxicity by reversing all the abnormal parameters to significant levels. Histopathological results revealed that RD leaf and bark extracts at 400 mg/kg protects the liver from damage induced by CCl4. The results of this study scientifically validate the traditional use of RD leaf and bark for the treatment of liver ailments.